PENGARUH RETURN ON ASSET, DEBT TO EQUITY RATIO, NET PROFIT MARGIN TERHADAP INCOME SMOOTHING DENGAN VARIABEL MODERASI PROPORSI WANITA DI DALAM DEWAN DIREKSI (STUDI KASUS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA TAHUN 2013-2015) - Yolita Kurniawati; Paulus Sulluk Kananlua; Sugeng Susetyo (Management Insight: Jurnal Ilmiah Manajemen, 2017)
This study aims to investigate the effect of: (1) Return on Asset (ROA), Debt to Equity Ratio (DER), Net Profit Margin (NPM), and the proportion of women in board of directors on income smoothing. (2) Further, this study also investigates the moderating effect of proportion of women in board of directors on effect of ROA, DER, and NPM to income smoothing. Data were collected from anufacture companies listed on the Indonesia Stock Exchange (IDX) in the year of 2013 -2015. Multiple regression analysis and moderated regression analysis were used to test the hypotesis in this study. The results of multiple regression analysis show that Return on Asset (ROA) and Debt to Equity Ratio (DER) influence the income smoothing. Meanwhile, Net Profit Margin (NPM) does not influence the income smoothing. The result of moderated regression analysis shows that the proportion of women does not moderate the effect of Return on Asset (ROA), Debt to Equity Ratio (DER), and Net Profit Margin (NPM) on income smoothing. Those could happen because very women are sit in the Board of Directors of the firms in Indonesia.Keywords: Income Smoothing, Return on Asset (ROA), Debt to Equity Ratio (DER), Net profit Margin (NPM).